2017
DOI: 10.9778/cmajo.20170039
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient and physician advocacy in reducing wait times for cancer care: a qualitative analysis

Abstract: Background: There is growing interest in the role of physician as health advocate; however, few studies have documented advocacy from the patient's perspective. To address this gap, we examined the experiences of patients with cancer from the onset of symptoms to the start of treatment in Newfoundland and Labrador and aimed to describe wait times and efforts to improve timeliness of care from the patients' perspective. Methods:We conducted qualitative interviews with 60 participants aged 19 years or more with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This finding is consistent with the role of self-advocacy in improving the quality of care for patients with cancer. 24 25 Previous studies suggested dismissive responses from PCPs may impact patients’ decisions to consult care again. 26 27 In contrast, our participants reported persistence and at times sought other providers.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the role of self-advocacy in improving the quality of care for patients with cancer. 24 25 Previous studies suggested dismissive responses from PCPs may impact patients’ decisions to consult care again. 26 27 In contrast, our participants reported persistence and at times sought other providers.…”
Section: Discussionmentioning
confidence: 99%
“…The time a patient spends in a health care facility includes time spent at various service stations, time spent waiting for the doctor, and the time spent with the doctor during consultations. An indication of improvement in the standard of surgical practices is the extent patients are satisfied with the time spent waiting for the doctor ( 37 ). Innovative approaches of improving patient waiting time in a complex multispecialty hospital like this setting involve deploying patient advocacy strategies to ensure access to timely and good quality care or improving the experiences of the patients while waiting through the provision of audiovisual or print entertainment systems ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%